2013
DOI: 10.1007/s11743-013-1547-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Some Triazole Derivatives as Corrosion Inhibitors and Biocides

Abstract: Three compounds namely; 5‐(phenyl)‐4H‐1,2,4‐triazole‐3‐thiol, 3‐(decylthio)‐5‐phenyl‐1H‐1,2,4‐triazole and 3‐(benzylthio)‐5‐phenyl‐1H‐1,2,4‐triazole) were synthesized. The chemical structure of the prepared compounds was confirmed using FTIR and 1H‐NMR analysis. The compounds were tested as corrosion inhibitors against the corrosion of carbon steel in 1 M HCl using weight loss, polarization and electrochemical impedance methods. The results revealed that these compounds have significant inhibiting effects on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 43 publications
0
21
0
1
Order By: Relevance
“…The polar head of the surfactant is functionalized with metal ions bound to and surrounded by a hydrophobic region, similar to the situation found in metalloproteinase [30]. Also, several workers have reported the used surfactants as antimicrobial agents [31][32][33][34]. In this work, two-membered cationic surfactants (C12Q and C16Q) and their Co(II), Sn(II) and Zn(II) complexes (C12QCo, C12QSn, C12QZn, C16QCo, C16QSn and C16QZn) were synthesized and evaluated for their potent action against different bacterial strains, including pathogenic bacteria, fungi and sulfate-reducing bacteria (SRB).…”
Section: Introductionmentioning
confidence: 93%
“…The polar head of the surfactant is functionalized with metal ions bound to and surrounded by a hydrophobic region, similar to the situation found in metalloproteinase [30]. Also, several workers have reported the used surfactants as antimicrobial agents [31][32][33][34]. In this work, two-membered cationic surfactants (C12Q and C16Q) and their Co(II), Sn(II) and Zn(II) complexes (C12QCo, C12QSn, C12QZn, C16QCo, C16QSn and C16QZn) were synthesized and evaluated for their potent action against different bacterial strains, including pathogenic bacteria, fungi and sulfate-reducing bacteria (SRB).…”
Section: Introductionmentioning
confidence: 93%
“…Equation (12) showed that, -E a /R is the slope of the straight line (ln k vs. 1/T), so the value of E a could elucidate the effect of temperature on corrosion inhibition. E a increased with increase in the inhibitors concentration, which further confirms that efficiency decreases with increase in temperature.…”
Section: Activation Parametersmentioning
confidence: 99%
“…Very low biodegradation percentages found for gemini surfactants with dodecane spacer length can be explained by assuming that dicationic substances with a high number of carbons (12) between the nitrogen and hydrophobic tail (giving a large hydrophobic moiety) are non-biodegradable. The highest biodegradation percentages were found with gemini surfactants obtained from G-2 because of small hydrophobic character.…”
Section: Biodegradationmentioning
confidence: 99%
See 1 more Smart Citation
“…These surfactants are characterized by their extreme tendency towards biodegradation, which means the degradation of organic compounds using microorganisms to produce compounds of low molecular weight, such as alcohols and short-chain fatty acids. The withdrawal of toxic and nonbiodegradable surfactants from commercial use and their replacement with green and biodegradable surfactants is highly necessary [18][19][20][21][22][23][24][25][26][27][28][29]. The aim of this study is to synthesize some non-ionic surfactants derived from vanillin (a natural compound) and to study their surface activity and biodegradability, and also to evaluate these compounds as corrosion inhibitors for carbon steel in 0.5-M hydrochloric acid (HCl).…”
Section: Introductionmentioning
confidence: 99%